From Folklore to Esotericism and Back: Neo-Paganism in Serbia - Radulovic, Nemanja (Pomegranate, 2017)
The article give an overview of Neo-Pagan scene in Serbia grouped in two camps, Wiccan and Slavic, while showing at the same time the fluid character of division. Broader cultural context (Romanticism and cultural reception of folklore) is provided as an interpretational key. Polarity esotericism/folklore reflect some deeper currents within national culture showing Neo-Paganism thus not to be "odd" or "fringe" but as an alternative variant of "mainstream" cultural concepts.